Deposits Activity as a Measure of Business Activity - Snyder, Carl (The Review of Economics and Statistics, 1924)
the new system of reporting debits to individual accounts in the larger cities of the country, inaugurated by the Federal Reserve Board. These reports, begun in the latter part of I9I8, represent an advance over the previous system of reporting interbank clearings only in that they gave the full amounts of the checks drawn in each of the reporting centers, though, as we shall see, the difference is in degree and not of kind. These rates of turnover were computed according to a formula worked out jointly by Professor Fisher, Professor Kemmerer, and Mr. J. H. Riddle, then of the department, and recorded the number of times which, on the average, a dollar of demand deposits in each of the various cities was paid out; that is, the amount of checks drawn each month against the average of demand